Green governance and sustainability report quality: The moderating role of sustainability commitment in ASEAN countries - Chairina Chairina; Bambang Tjahjadi (Economies, 2023)
This study aims to examine the role of green governance in the quality of sustainability reports. We also examine the moderating role of sustainability commitment between green governance and the quality of sustainability reports. This research is a quantitative study by using unbalanced data panels. The study retrieves the samples from the companies listed on the ASEAN Stock Exchange that published sustainability reports from 2015 to 2019. The research finding shows that the board's independence, board diversity, and sustainability commitment are significantly associated with the quality sustainability reports. Moreover, the board size indicates a low effect on the reliability and the chief sustainability officer on the conciseness of sustainability reports. Meanwhile, it has not been possible to prove that the presence of sustainability committee can lead effect on the report quality. The sustainability commitment also moderates female directors and the quality of sustainability reports. Other findings are obtained from the company's characteristics where company size and type of industry are positively correlated with the quality of sustainability reports. This study has several limitations. First, some companies that are under observation spend money on social costs, but the amounts are not clearly disclosed. Second, this research only focuses on three quality aspects: conciseness, clarity, and reliability. These research findings contribute to the following scopes. First, how green governance and commitment to sustainability help improve the quality of corporate reporting. Second, the investors should invest in companies that apply good green governance and sustainability commitment. Third, companies with strong commitments to sustainability and good corporate governance are competitive resources that support businesses in growing, attracting more investment, and earning stakeholders' trust. Lastly, this research also contributes to the agency and the resource-based view theories related to the green governance and the sustainability reports' quality of ASEAN countries.
Keywords: 330; ASEAN countries; green governance; sustainability commitment; sustainability report quality